2012
DOI: 10.1088/1674-1056/21/4/047804
|View full text |Cite
|
Sign up to set email alerts
|

Size-dependent nonlinear absorption and refraction of Ag nanoparticles excited by femtosecond lasers

Abstract: Silver (Ag) nanoparticles with different average sizes are prepared, and the nonlinear absorption and refraction of these nanoparticles are investigated with femtosecond laser pulses at 800 nm. The smallest Ag nanoparticles show insignificant nonlinear absorption, whereas the larger ones show saturable absorption. By considering the previously reported positive nonlinear absorption of 9 nm Ag nanoparticles, the nonlinear absorptions of Ag nanoparticles are found to be size-dependent. All these nonlinear absorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…The UV-Vis absorption spectrum of AgNPs is shown in Figure 2. It can be seen from Figure 2 that AgNPs have a strong absorption band at about 410 nm, which can be attributed to the SPR of AgNPs [12,13,26]. The TEM image of AgNPs is shown in Figure 3 and it can be determined that the average diameter of AgNPs is about 10 nm.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…The UV-Vis absorption spectrum of AgNPs is shown in Figure 2. It can be seen from Figure 2 that AgNPs have a strong absorption band at about 410 nm, which can be attributed to the SPR of AgNPs [12,13,26]. The TEM image of AgNPs is shown in Figure 3 and it can be determined that the average diameter of AgNPs is about 10 nm.…”
Section: Resultsmentioning
confidence: 90%
“…The NLO effect of noble metal nanoparticles is greatly enhanced due to their unique localized surface plasmon resonance (LSPR) behaviour [7][8][9][10]. The nonlinear refractive properties of gold, silver and other noble metal nanoparticles have been widely studied [10][11][12][13][14][15][16][17][18][19][20]. It has been reported that the nonlinear refractive index of composite materials with noble metal nanoparticles is greatly enhanced due to the effect of noble metal nanoparticles [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…However, the chemical reactions are very different once one considers the nano- and macro-scale structures [17,18,19]. In the case of nanoscale, studies have shown that morphology [20,21] and sizes of particles [22,23,24] have an impact on their chemical properties. Therefore, it is worth studying the dynamics of morphology and particle sizes of Al, aluminum oxide, and hydrolysates at the nanometer level.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of the nonlinear absorption coefficients and nonlinear refractive indices of Ag NPs, as well as the exploration of their potential applications, was reported in a few studies [17][18][19]. There are experimental studies showing that particle size, morphology, and surrounding medium of noble metal NPs have great influence on their nonlinear optical properties [20][21][22][23]. For example, Ag NPs with smaller particle sizes demonstrated weak nonlinear optical response, while larger particles were characterized by strong saturable absorption (SA) [20].…”
Section: Introductionmentioning
confidence: 99%
“…There are experimental studies showing that particle size, morphology, and surrounding medium of noble metal NPs have great influence on their nonlinear optical properties [20][21][22][23]. For example, Ag NPs with smaller particle sizes demonstrated weak nonlinear optical response, while larger particles were characterized by strong saturable absorption (SA) [20]. With the increase of particle sizes, nonlinear absorption has shown a shift from two-photon absorption (2PA) to SA, while nonlinear refraction was transformed from self-defocusing to self-focusing [21].…”
Section: Introductionmentioning
confidence: 99%